A systematic, inquiry-based 7-Step Virtual Worlds Teacher Training. (September 2015) - Nussli, Natalie Christina; Oh, Kevin
Eighteen special education teachers explored one prominent example of three-dimensional virtual worlds, namely Second Life. This study aimed to (a) determine their perception of the effectiveness of a systematic 7-Step Virtual Worlds Teacher Training workshop in terms of enabling them to make informed decisions about the usability of virtual worlds for students with social skills challenges and (b) determine whether there was a teacher change of attitude resulting from engagement in this systematic workshop. The seven steps are described in detail. The teachers' change of attitude was statistically significant with a large effect size. The teachers' feedback on the effectiveness of the training program resulted in 14 practical guidelines, which informed the revised 4-Step Virtual Worlds Teacher Training model that can be used both in general and special education with minor adjustments depending on the teacher and student population.